Development and application of a duplex real‐time PCR assay for differentiation of genotypes I and II African swine fever viruses. Issue 5 (28th January 2022) - Li, Xiangdong; Hu, Yongxin; Liu, Penggang; Zhu, Zhenbang; Liu, Paorao; Chen, Changhai; Wu, Xiaodong
Abstract: Genotype II African swine fever virus (ASFV) has been plaguing Chinese pig industry and caused severe morbidity and mortality of pigs resulting in huge economic losses since its first report in August 2018. Most recently, two genotype I ASFVs with low virulence but efficient transmissibility in pigs were reported in China, which makes the diagnosis and control of this lethal disease more challenging. Therefore, it is prerequisite and important to differentiate genotype I from genotype II upon ASFV outbreaks before making any stringent control procedures. In this study, a duplex real‐time PCR assay based on ASFV E296R gene was established which could simultaneously detect genotypes I and II ASFVs with two pairs of primers and two probes. Plasmid containing ASFV genes was used to test the sensitivity, repeatability, and reproducibility. DNA or cDNA samples of ASFV and other swine viruses were used to test the specificity. The results showed that the established duplex real‐time PCR assay has satisfied specificity, sensitivity, repeatability, and reproducibility. In addition, the assay was applied to differentiate 84 ASFV positive clinical samples including lymph nodes, spleen, kidney, lung, liver, blood, nasal swab, and environmental swab samples which were sent to National ASF Reference Laboratory from April 2020 to September 2021. The results showed that all these ASFV positive samples belong to genotype II ASFV. The established duplex real‐time PCR in this study provides a powerful tool for rapid detection and differentiation between genotypes I and II ASFVs and will facilitate efficient control of ASFV in China.